Frequency variability of standing Alfvén waves excited by fast mode resonances in the outer magnetosphere. Issue 23 (14th December 2015) - Archer, M. O.; Hartinger, M. D.; Walsh, B. M.; Plaschke, F.; Angelopoulos, V.
Abstract: Coupled fast mode resonances (cFMRs) in the outer magnetosphere, between the magnetopause and a turning point, are often invoked to explain observed discrete frequency field line resonances. We quantify their frequency variability, applying cFMR theory to a realistic magnetic field model and magnetospheric density profiles observed over almost half a solar cycle. Our calculations show that cFMRs are most likely around dawn, since the plasmaspheric plumes and extended plasmaspheres often found at noon and dusk can preclude their occurrence. The relative spread (median absolute deviation divided by the median) in eigenfrequencies is estimated to be 28%, 72%, and 55% at dawn, noon, and dusk, respectively, with the latter two chiefly due to density. Finally, at dawn we show that the observed bimodal density distribution results in bimodal cFMR frequencies, whereby the secondary peaks are consistent with the so‐called "CMS" frequencies that have previously been attributed to cFMRs. Key Points: Dawn‐dusk asymmetry in outer magnetospheric density results in FMRs being more likely around dawn Relative spread in FMR frequencies is estimated to be 28% (dawn), 72% (noon), and 55% (dusk) Bimodal density distribution at dawn yields secondary peaks in FMR frequencies consistent with CMS